Basketball Dribbling Training at SMP 3 Bontomannu: Efforts to Improve Basic Technical Skills and Student Confidence - Suwardi, Suwardi; Badaru, Benny; Juhanis, Juhanis (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2025)
Basketball dribbling training at SMP 3 Bontomannu was designed to develop students' basic technical competencies in ball control and build confidence in playing basketball. This program provides opportunities for students to understand the fundamental principles of dribbling, recognize variations in ball control techniques, learn strategies for applying dribbling in game situations, and develop motor coordination and agility. Through structured and progressive training, it is expected that students can improve ball handling abilities, develop decision-making skills in games, increase physical fitness, and foster sportsmanship and teamwork in the school environment.